Employee Attrition Prediction - Benson Antony D V; Haritha Rajeev, (Indian Journal of Data Mining (IJDM), 2024)
Employee attrition occurs when a worker leaves a company to join another firm for a better offer. It might also be referred to as Employee Defection. Representative downsizing is likely to be significant when there is a pressing demand for workers in a particular industry due to mass retirements or organizational growth. At one point, the programming industry had significant attrition rates due to abundant job opportunities in the software sector driven by the demand for software products across all industries. Reducing the employee attrition rate is a challenging challenge faced by HR managers. This study provides a clear viewpoint on predicting employee turnover using Machine Learning methods. The projection is completed using data obtained from IBM HR analysis. We employed Logistic Regression for the analysis and achieved an accuracy rate of 87%.